The poppy wife : [large type] a novel of the Great War - Scott, Caroline (Thorndike Press large basic, 2020)
"In the tradition of Jennifer Robson and Hazel Gaynor, this unforgettable debut novel is a sweeping tale of forbidden love, profound loss, and the startling truth of the broken families left behind in the wake of World War I. 1921. Survivors of the Great War are desperately trying to piece together the fragments of their broken lives. While many have been reunited with their loved ones, Edie's husband Francis has not come home. Francis is presumed to have been killed in action, but Edie believes he might still be alive. Harry, Francis's brother, was there the day Francis was wounded. He was certain it was a fatal wound--that he saw his brother die--but as time passes, Harry begins questioning his memory of what happened. Could Francis, like many soldiers, merely be lost and confused somewhere? Hired by grieving families, Harry returns to the Western Front to photograph gravesites. As he travels through battle-scarred France and Belgium gathering news for British wives and mothers, he searches for evidence of Francis. When Edie receives a mysterious photograph of Francis, she is more convinced than ever he might still be alive. And so, she embarks on a journey in the hope of finding some trace of her husband. Is he truly gone? And if he isn't, then why hasn't he come home? As Harry and Edie's paths converge, they get closer to the truth about Francis and, as they do, are faced with the life-changing impact of the answers they discover. Artful and incredibly moving, The Poppy Wife tells the unforgettable story of the soldiers lost amid the chaos and ruins, and those who were desperate to find them"--